PENGARUH EXPRESSIVE WRITING THERAPY TERHADAP KECEMASAN PADA PENGGUNA NARKOBA - Pastari, Marta; Martini, Sri; Endriyani, Sri (Poltekkes Kemenkes Palembang, 2023)
Background: One of the therapies that can be given to overcome anxiety in drug users is expressive writing therapy, which is an activity of writing with the deepest and most emotional ideas and feelings without being concerned with research procedures such as spelling, grammar, or other writing conventions. The purpose of this study was to determine the effect of expressive writing therapy on anxiety in drug users. Methods: The design used in this study was pre-experimental with a one-group pretest-posttest design approach. Total population and sample of 27 respondents (1 treatment group) using total sampling technique. In this design, the treatment group was given expressive writing therapy and their anxiety scale was measured using the Zung Self-Rating Anxiety Scale (SAS/SRAS) which was implemented at the Ar-Rahman Palembang Drug Rehabilitation Center Foundation. Results: The results of this study indicate that there is an effect of giving expressive writing therapy on the anxiety of drug users which is marked by a decrease in anxiety scores and subjective and objective responses of drug users. Conclusion: Expressive writing therapy has an effect on anxiety in drug users.